study of the differences in the Motor coordination and dynamic balance among primary school students according to age, gender, and Urban area - بوطبية عومار (Journal of Sport Science Technology and Physical Activities, 2025)
The study aimed to identify the differences in some motor skills among primary school students according to age, gender and region. The analytical descriptive method was used to provide solutions to the research questions relying on the eye-hand coordination and dynamic balance tests to collecting data from40 students from the municipality of El Mahmal. The study concluded a statistically significant differences in hand-eye coordination and dynamic balance attributed to the variables of age and gender in the study sample, the researcher recommend to providing the necessary spaces ; means and increasing the number of weekly classes allocated to physical education and sports. He also suggested Conduct similar studies on various motor and coordination skills